2020
DOI: 10.21203/rs.3.rs-109527/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diarrhoeal diseases in Soweto, South Africa, 2020: a community survey

Abstract: Background In South Africa, there are limited data on the burden of diarrhoea at a community level, specifically in older children and adults. This community survey estimated rates of and risk factors for diarrhoea across all ages and determined the proportion of cases presenting to healthcare facilities. Methods Randomly sampled households were enrolled from an existing urban health and demographic surveillance site. A household representative was interviewed to determine risk factors and occurrence of diarrh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Guided by the P-E hypothesis, this study identified factors influencing the health and well-being of older adults residing in two contrasting residential neighborhoods in Accra, Ghana. The reported susceptibility of older slum and non-slum dwellers to infectious and parasitic diseases is consistent with findings from previous studies with older urban populations in the region (49,50). However, in low-income urban communities such as slums, older adults' vulnerability to such inflictions is likely to be higher, given what may appear to be a mismatch between their personal competences and the environmental press presented by the residential settings in which they live (23).…”
Section: Discussionsupporting
confidence: 88%
“…Guided by the P-E hypothesis, this study identified factors influencing the health and well-being of older adults residing in two contrasting residential neighborhoods in Accra, Ghana. The reported susceptibility of older slum and non-slum dwellers to infectious and parasitic diseases is consistent with findings from previous studies with older urban populations in the region (49,50). However, in low-income urban communities such as slums, older adults' vulnerability to such inflictions is likely to be higher, given what may appear to be a mismatch between their personal competences and the environmental press presented by the residential settings in which they live (23).…”
Section: Discussionsupporting
confidence: 88%
“…Several interventions have been in place to tackle diarrhea risk factors [ 12 ] including the use of rotavirus vaccine, support and promotion of exclusive breastfeeding at least in the first six months of a the child’s life, good community health literacy programs on how to manage and prevent diarrhea episodes and keep the children healthy through the use of oral rehydration solution (ORS) used to replace lost fluid as a result of dehydration, good hand washing with soap, use of safe drinking water and proper food and water storage containers [ 2 , 5 , 13 , 14 ]. According to the WHO/UNICEF [ 15 ], these proven interventions are yet to make progressive impacts to those at risk in the rural communities.…”
Section: Introductionmentioning
confidence: 99%